The impact of sex education on teenage pregnancy in basic schools of Bawku municipal district in Ghana - Donkor, Anthony Kudjo; Lariba, Azure Love (University of Muhammadiyah Malang, 2017)
The incidence of teenage pregnancy has been on the rise in Ghana, especially in the Bawku-East Municipality. In Ghana adults rarely discussed sexual matters with the youth. Thus, the youth have little or no information about the biological changes that take place in their bodies during the transitional period from youth to adulthood. This has resulted in unplanned pregnancies for the vast majority of teenagers, which have serious developmental and socioeconomic implications. The study was to explore how sex education could mitigate teenage pregnancy in the Bawku-East Municipality. A total sample size of one hundred and twenty-five (125) respondents was used for the study. Questionnaires, in-depth interviews, focus group discussions and observation were used to collect data for the study. The study revealed that poor parenting, poverty and peer influence were the major causes of teenage pregnancy in the study area. In addition, concealing sex education and sex-knowledge from the youth made them more curious and vulnerable. There is the need for parents and schools to empower the youth through sex education to equip them with knowledge in order to overcome the potentially corrupt information through the social media and friends. The study will be useful to students, parents, teachers and vulnerable group (girl-child) advocates in communities.